2014
DOI: 10.1093/nar/gku601
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage triggers SAF-A and RNA biogenesis factors exclusion from chromatin coupled to R-loops removal

Abstract: We previously identified the heterogeneous ribonucleoprotein SAF-A/hnRNP U as a substrate for DNA-PK, a protein kinase involved in DNA damage response (DDR). Using laser micro-irradiation in human cells, we report here that SAF-A exhibits a two-phase dynamics at sites of DNA damage, with a rapid and transient recruitment followed by a prolonged exclusion. SAF-A recruitment corresponds to its binding to Poly(ADP-ribose) while its exclusion is dependent on the activity of ATM, ATR and DNA-PK and reflects the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
169
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(181 citation statements)
references
References 85 publications
(101 reference statements)
12
169
0
Order By: Relevance
“…The ChIP signal was the same at R-loops from wildtype and catalytically dead RNase H1. If RNase H1 were active on most hybrids where it was bound, one might expect it to degrade the hybrids and interact transiently, whereas the catalytically dead RNase H1, being unable to degrade the hybrids, would have a prolonged interaction and generate a higher ChIP signal (17,18). However, this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…The ChIP signal was the same at R-loops from wildtype and catalytically dead RNase H1. If RNase H1 were active on most hybrids where it was bound, one might expect it to degrade the hybrids and interact transiently, whereas the catalytically dead RNase H1, being unable to degrade the hybrids, would have a prolonged interaction and generate a higher ChIP signal (17,18). However, this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that cotranscriptional R-loops contribute to DSB formation, possibly due to collisions between the replication and transcription machineries at the unresolved R-loops (13)(14)(15). In addition, Rloops as detected by RNase H recruitment have also been observed at micro-IR-induced DNA lesions immediately following DNA damage (20).…”
Section: Discussionmentioning
confidence: 99%
“…Second, although others have shown that R-loops and R-loop-induced phenotypes can be suppressed by overexpression of RNase H (17,18,54), RNase H overexpression did not compensate for DDX1 depletion as measured by the DR-GFP reporter assay. Third, recruitment of RNase H and other R-loop-associated factors to DNA lesions induced by micro-IR is rapid but transient (recruitment occurs within minutes, with factors then dissociating from the DNA lesions) (20), whereas DDX1 accumulation at DSBs follows much slower kinetics (peaks at 1 h, with no dissociation detected for hours), suggesting that RNase H and DDX1 either play different roles or act at different stages in resolving RNA-DNA structures during the DSB repair process. Fourth, senataxin, an RNA helicase that plays a critical role in resolving R-loops in vivo (54,64), did not coimmunoprecipitate with DDX1 in either the presence or absence of IR-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations